Preparation method and application of active cationic chitosan nanoparticles
By reacting aldehyde compounds on chitosan to form Schiff base protection, and grafting quaternary ammonium salt groups at C6 and acrylic acid at C3, crosslinked chitosan nanoparticles are formed through hydrothermal reaction, solving the problem of using acid solutions and chemical crosslinking agents in the prior art, achieving green modification of chitosan and improving textile performance.
Patent Information
- Application Number
- CN202411800604.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art has the problem of using acid solutions and chemical crosslinking agents in the application of chitosan, which leads to environmental pollution and adverse effects on natural fibers. The antibacterial properties and cationic properties of chitosan are easily destroyed during the quaternization process.
The reaction of aldehyde compounds is used to form the Schiff base to protect the amino group of chitosan C2, quaternary ammonium salt groups are grafted at the C6 position, and acrylic acid is grafted at the C3 position. Through hydrothermal reaction, the carboxylate anion of acrylic acid is cross-linked and assembled with chitosan cations to form chitosan nanoparticles with high activity and strong stability.
The green modification of chitosan is achieved, which improves the antibacterial, moisture-absorbing and breathable and environmentally friendly dyeing properties of textiles, avoids the use of chemical crosslinking agents, and ensures the protection of natural fibers and environmental friendliness.
Smart Images

Figure BDA0005177959070000031 
Figure BDA0005177959070000151 
Figure BDA0005177959070000152
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional finishing textiles, in particular to a modified fabric with active cationic chitosan nanoparticles in situ grafted. Background Art
[0002] Chitosan is a biopolymer abundant in nature. It is widely used in textile printing and dyeing, daily chemical industry, industrial wastewater treatment, biomedicine and other fields because of its wide sources, renewable, biocompatible, non-toxic and non-irritating, high-efficiency and long-lasting antibacterial ability, broad antibacterial spectrum, safety and hygiene. The strong hydrogen bonding within and between chitosan molecules makes it difficult to dissolve in water and can only be dissolved in acidic solutions. Acidic solutions are volatile, highly corrosive, and pollute the environment, which greatly limits the application of chitosan. At the same time, there is a lack of effective chemical crosslinking between chitosan and fiber materials. The main method at present is to chemically graft chitosan to the surface of fiber or fabric through the bridging effect of crosslinking agents such as aldehydes, epoxy resins or polycarboxylic acids [Ferrero F, Periolatto M, Burelli S, Carletto RA. Silk grafting with chitosan and crosslinking agents. Fibers and Polymers, 2010, 11 (2): 185-192]. However, the crosslinking agent will coat a layer of chemical substances on the surface of the fabric, resulting in "chemical fiberization" of the natural fiber surface, which has a negative impact on the excellent properties of natural fibers and human health; and the chemical crosslinking agent needs to be baked at high temperature (150-175°C) to undergo esterification crosslinking reaction, which can easily cause problems such as strength loss and yellowing of the fabric. Therefore, it has become a hot topic to explore the green modification method of chitosan without crosslinking agents and acid solutions to give textiles good performance and multifunctionality.
[0003] The study of chitosan quaternization is an important direction of chitosan chemical modification at present. By quaternizing the amino or hydroxyl groups on the chitosan molecules, the quaternary ammonium salt groups with large steric hindrance and strong hydration ability are introduced into the macromolecular chain, which enhances the water solubility of chitosan derivatives and has better adsorption performance [Manubolu M, Pathakoti K, Leszczynski J. Recent advances in chitosan-based nanocomposites for dye removal: areview. International Journal of Environmental Science and Technology, 2024, 21: 4685-4704]. In recent years, quaternization or grafting of quaternary ammonium salts on the C2 amino group of chitosan molecules has attracted the attention of many scholars. Using 3-chloro-2-hydroxypropyltrimethylammonium chloride, the -NH2 at the C2 position of chitosan is replaced by an emulsion cross-linking reaction to obtain an N-quaternized chitosan product. Some scholars have also introduced alkyl chains of different lengths into chitosan molecules by first forming a Schiff base on the -NH2 of chitosan molecules and then reducing the Schiff base. However, these methods have long reaction cycles and consume a large amount of chitosan amino groups during the reaction, which destroys the natural antibacterial properties and cationic properties of chitosan [Lim SH, Hudson SM. Review of chitosan and its derivatives as antimicrobial agents and their uses as textile chemicals. Journal of Macromolecular Science, 2003, 43(2): 233-269].
[0004] The emergence of nanotechnology has expanded the application scope of chitosan. Chitosan nanoparticles show a unique nano-small size effect. Their chemical reactivity, biological activity, adsorption and specific surface area are greatly improved, and their solubility in neutral solution is significantly improved, making them very suitable as functional finishing agents for textiles. Invention patent CN102677465B discloses a functionalized nano-chitosan and nano-titanium dioxide modified tussah silk fabric and its preparation method, which uses an acid solution to dissolve chitosan, drips sodium tripolyphosphate solution and nano-titanium dioxide sol, and obtains chitosan / titanium dioxide composite nano finishing liquid with a particle size of less than 100nm after strong stirring to treat tussah silk fabric. However, the preparation process of this method is complicated, butane tetracarboxylic acid, polymaleic acid and tartaric acid are used as cross-linking agents and hypophosphite is used as a catalyst, and the tussah silk fabric is baked at a high temperature of 165-170°C, which has an adverse effect on the biological activity and wearing performance of tussah silk. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention aims to provide a method for preparing active cationic chitosan nanoparticles and its application in functional finishing fabrics. The present invention adopts aldehyde compound reaction to form Schiff base to protect the amino group at C2 position of chitosan, grafts quaternary ammonium salt group at C6 position, and grafts acrylic acid at C3 position to obtain acrylic acid quaternary ammonium salt chitosan, and utilizes hydrothermal reaction to make the carboxylate anion of acrylic acid and the cation of chitosan cross-link and assemble to form chitosan nanoparticles with high activity and strong stability. Acrylic acid quaternary ammonium salt chitosan is an amphoteric polyelectrolyte with good water solubility, biocompatibility, degradability, reactivity, and environmental friendliness, green and non-toxic characteristics, and has great application potential. The prepared nano acrylic acid quaternary ammonium salt chitosan has small particle size, uniform size, strong stability, high reactivity, can be used to adsorb heavy metal ions in wastewater, and effectively realizes the functional modification of textiles, and improves the antibacterial, environmentally friendly salt-free dyeing, moisture absorption and breathability of fabrics.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] The invention firstly discloses an active cationic chitosan nanoparticle, which is prepared by reacting a triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) solution of low molecular weight chitosan with an ethanol solution of an aldehyde compound to form a Schiff base protection at the amino group at the C2 position of chitosan, then reacting with 2,3-epoxypropyltrimethylammonium chloride in the presence of an alkaline catalyst to carry out a nucleophilic substitution reaction at the C6 position of chitosan, then adding a chemical initiator to graft with acrylic acid at the C3 position of chitosan, then removing the Schiff base protection at the C2 position of chitosan, and cross-linking and self-assembling the carboxylate anion of acrylic acid with the cation of chitosan through a hydrothermal reaction to obtain the active cationic chitosan nanoparticle.
[0008] The method for preparing the above active cationic chitosan nanoparticles comprises the following steps:
[0009] (1) Low molecular weight chitosan with a viscosity average molecular weight of 6300 to 18200 is dissolved in 80 to 120 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 1% to 4%, and 20 to 60 mL of anhydrous ethanol is added. The ethanol solution of an aldehyde compound is added dropwise under continuous stirring for 20 to 30 minutes to make the mass ratio of chitosan to the aldehyde compound be 1:1 to 9, and then heated and stirred at 60 to 80° C. for 8 to 12 hours. After cooling, 0.4 mol / L NaOH solution is added dropwise with stirring to adjust the pH to neutral, and light yellow chitosan Schiff base is obtained after suction filtration, ethanol ultrasonic washing, and vacuum drying; the aldehyde compound is salicylaldehyde, vanillin, cinnamaldehyde or fatty aldehyde.
[0010] (2) The chitosan Schiff base is placed in a three-necked flask, 30-50 mL of an alkaline catalyst solution with a mass concentration of 0.08-0.4% is added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride is added dropwise within 30-50 minutes, and then stirred to react at 60-90° C. for 1-4 hours, and the obtained viscous product is precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with an ethanol solution with a mass concentration of 75-90% for 30-40 minutes, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base; the molar ratio of the chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride is 1:0.5-5, and the alkaline catalyst is 1-butyl-3-methylimidazolium hydroxide ionic liquid ([Bmim]OH).
[0011] (3) dissolving the quaternary ammonium salt chitosan Schiff base obtained in step (2) in 15 mL of an acrylic acid solution having a mass concentration of 10 to 20%, then adding an initiator 4-methoxyphenol and an acidic catalyst ammonium chloride, stirring and reacting for 5 to 15 minutes under microwave irradiation, then adding 30 to 45 mL of methanol and stirring for 1 to 3 minutes, finally adding acetone for precipitation, filtering and washing with a mixed solution of acetone and ethanol in a volume ratio of 1:1, filtering with ether, vacuum drying at 40 to 60° C. for 8 to 10 hours, and ball milling to obtain an acrylic acid-based quaternary ammonium salt chitosan Schiff base. The powder is placed in a 0.2-0.4 mol / L hydrochloric acid ethanol solution, and the ethanol is evaporated and removed after rotating and stirring for 18-20 hours. A light yellow acrylic acid-based quaternary ammonium salt chitosan (i.e., active cationic chitosan) is obtained after acetone precipitation, suction filtration, vacuum drying, and ball milling. The molar ratio of the quaternary ammonium salt chitosan Schiff base to acrylic acid is 1:4-10, the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol is 80-100:1, and the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride is 1.2-5.8:1.
[0012] (4) dissolving the acrylic acid quaternary ammonium salt chitosan obtained in step (3) in an acetic acid solution with a pH of 3.2 to 5.4 to make its mass concentration 0.03 to 1.2%, performing ultrasonic cavitation treatment for 6 to 10 minutes using an ultrasonic cell pulverizer with a power of 160 to 300 W to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, then heating to 80 to 110° C. and stirring for 40 to 90 minutes to carry out hydrothermal reaction to make the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules cross-linked with the cationic quaternary ammonium salt and amino groups and electrostatically assemble to form nanoparticles, cooling to room temperature and standing for 1 to 2 hours to obtain a stable and uniform dispersion of active cationic chitosan nanoparticles (i.e., acrylic acid quaternary ammonium salt chitosan nanoparticles), at which time the solution exhibits opalescence; the active cationic chitosan nanoparticles have an average particle size of 106 to 181 nm and a Zeta potential of 28.65 to 45.39 mV.
[0013] Preferably, the acrylic acid quaternary ammonium salt chitosan (active cationic chitosan) in step (3) has a viscosity-average molecular weight of 9620-26075, a C3 acrylic acid grafting rate of 61.03-82.37%, a C2 deacetylation degree of ≥92.41%, a C6 quaternary ammonium salt substitution degree of 69.60-89.16%, and a solubility in water of ≥27.58 g / 100 mL; the structural formula of the acrylic acid quaternary ammonium salt chitosan is as follows:
[0014]
[0015] Preferably, in step (1) and step (2), the ultrasonic power of ultrasonic washing is 160 to 280 W.
[0016] Preferably, in step (3), the microwave radiation power is 420-780 W, and the microwave radiation temperature is 100-120° C.
[0017] The active cationic chitosan nanoparticles prepared by the present invention can be applied to functional finishing fabrics. Based on this, the present invention further provides a method for preparing fabrics modified by active cationic chitosan nanoparticles, which comprises subjecting the fabrics after scouring, desizing or degumming to an amide crosslinking reaction with nano acrylic acid quaternary ammonium salt chitosan to in-situ generate a nano acrylic acid quaternary ammonium salt chitosan coating on the fabric surface. The method specifically comprises the following steps:
[0018] (1) The desized or degummed fabric is added to a dispersion of active cationic chitosan nanoparticles with a mass concentration of 0.2 to 1.2% at a bath ratio of 1 g: 30 to 50 mL, and the reaction is continuously stirred at 30 to 60° C. for 0.5 to 4 h to allow the nano-acrylic acid quaternary ammonium salt chitosan to undergo an amide cross-linking reaction with the fabric, and a nano-acrylic acid quaternary ammonium salt chitosan coating is in situ generated on the surface of the fabric. The fabric is then dipped and rolled twice using an electric rolling mill to allow the liquid carrying rate of the modified fabric to be 70 to 90%.
[0019] (2) pre-drying the fabric obtained in step (1) at 50-70° C. for 20-35 minutes, stagnating for 5-8 minutes, and then vacuum drying at 45-60° C. for 3-6 hours, filtering and washing the modified fabric with an acetone solution having a mass concentration of 40-60% to remove the unreacted nano-quaternary ammonium salt chitosan, and then washing with deionized water, dehydrating, and air-drying to obtain a fabric modified with active cationic chitosan nanoparticles. The modified fabric has the advantages of moisture absorption and breathability, affinity with the human body, comfort, long-lasting antibacterial effect, and salt-free environmentally friendly dyeing.
[0020] Preferably, in step (1), acetic acid and sodium acetate buffer are used to control the pH of the active cationic chitosan nanoparticle dispersion to 4.0-5.2.
[0021] Preferably, the loading amount of active cationic chitosan nanoparticles in the modified fabric is 6.94-11.38%.
[0022] Preferably, the fabric of the present invention is one of a protein fiber fabric, a protein fiber and cellulose fiber blended fabric, and a protein fiber and chemical fiber blended fabric.
[0023] The active cationic chitosan nanoparticle modified fabric of the invention can be used in salt-free environmentally friendly dyeing of active dyes and acid dyes.
[0024] The active cationic chitosan nanoparticles of the present invention can also be used to adsorb Cu 2+ and / or Cr 6+ And other heavy metals.
[0025] In the preparation process of active cationic chitosan nanoparticles, by optimizing the viscosity average molecular weight of acrylic acid quaternary ammonium salt chitosan (active cationic chitosan), ultrasonic cavitation treatment time, C3 acrylic acid grafting rate, C6 quaternary ammonium salt substitution degree and C2 deacetylation degree, a series of active cationic chitosan nanoparticles with different particle sizes can be obtained. In the preparation process of active cationic chitosan nanoparticle modified fabrics, by optimizing the mass concentration of active cationic chitosan nanoparticles, reaction temperature and time, fabric liquid carrying rate, vacuum drying temperature and time, a series of modified fabrics with different grafting rates can be obtained.
[0026] Compared with the prior art, the principles and advantages of the preparation of active cationic chitosan nanoparticles and their application in functional finishing fabrics in the present invention are as follows:
[0027] 1. The present invention adopts triethylamine hydrogen sulfate ([(C2H5)3NH]HSO4) acidic ionic liquid as the dissolution and reaction medium of chitosan. The water produced in the Schiff base reaction between the amino group at the C2 position of chitosan and the ethanol solution of the aldehyde compound can be absorbed by the ionic liquid, which promotes the forward progress of the Schiff base reaction; at the same time, the triethylamine hydrogen sulfate ([(C2H5)3NH]HSO4) acidic ionic liquid makes the amino group at the C2 position of chitosan carry a positive charge, enhances the probability of nucleophilic reaction with the aldehyde compound, accelerates the reaction rate, can effectively form Schiff base protection at the amino group at the C2 position of chitosan, and promotes the substitution reaction of the primary hydroxyl group at the C6 position of chitosan with 2,3-epoxypropyltrimethylammonium chloride to form a quaternary ammonium salt. In addition, the aldehyde compounds such as salicylaldehyde, vanillin, cinnamaldehyde or fatty aldehyde used in the present invention have low molecular weight, small steric hindrance, are easy to contact and react with the amino group at the C2 position of chitosan, and are green, environmentally friendly and non-toxic.
[0028] 2. The present invention utilizes triethylamine hydrogen sulfate ([(C2H5)3NH]HSO4) ionic liquid as a green solvent for chitosan and a reaction medium for grafted aldehyde compounds. The ionic liquid has the advantages of being non-toxic and pollution-free, having stable physical and chemical properties, having no evaporation pressure and being non-volatile, being green and environmentally friendly, and being recyclable. The ionic liquid triethylamine hydrogen sulfate can directly dissolve chitosan under heating conditions without degrading or destroying the chitosan molecular chain. Anhydrous ethanol is added to the ionic liquid after the reaction to precipitate the remaining chitosan, and the chitosan can be recycled after evaporating and removing the anhydrous ethanol, which is environmentally friendly.
[0029] 3. The present invention uses 1-butyl-3-methylimidazolium hydroxide ionic liquid ([Bmim]OH) as an alkaline catalyst, which can promote the primary hydroxyl group at the C6 position in the chitosan Schiff base and the phenolic hydroxyl group of the aldehyde compound to form oxygen anions and phenol oxygen anions respectively under alkaline conditions, making it easier for quaternary ammonium salt substitution reaction to occur; at the same time, the 1-butyl-3-methylimidazolium hydroxide ionic liquid solution can fully swell the chitosan Schiff base, promote the active groups in the chitosan to be exposed, increase the probability of contact with the quaternary ammonium salt group, accelerate the nucleophilic substitution reaction, and significantly improve the quaternary ammonium salt substitution degree at the C6 position in the chitosan Schiff base.
[0030] 4. The present invention dissolves the quaternary ammonium salt chitosan Schiff base in an acrylic acid solution under microwave irradiation conditions for reaction. Due to the fast microwave irradiation heating speed, short reaction time and good uniformity, the C3 hydroxyl group of the quaternary ammonium salt chitosan Schiff base is fully in contact with the C=C double bond of acrylic acid, significantly improving the addition reaction rate and effectively increasing the grafting rate of acrylic acid. At the same time, the microwave irradiation reaction conditions are mild, the process is simple, the production cost is low, the efficiency is high, and the energy consumption is low. The present invention utilizes the initiator 4-methoxyphenol to promote the addition reaction of acrylic acid and the C3 hydroxyl group of the quaternary ammonium salt chitosan Schiff base, and the addition of the acidic catalyst ammonium chloride can release hydrochloric acid at a higher temperature, so that the C2 amino group of the quaternary ammonium salt chitosan Schiff base is protonated, effectively preventing the C2 amino group from reacting with acrylic acid, and the large steric hindrance of the Schiff base formed by the C2 amino group of chitosan also prevents the reaction from proceeding. Therefore, the grafting reaction of quaternary ammonium chitosan Schiff base with acrylic acid mainly occurs at the C3 secondary hydroxyl group of chitosan. At the same time, the quaternary ammonium chitosan grafted with acrylic acid can undergo amide cross-linking reaction with the amino group of protein fiber in an acidic environment.
[0031] 5. The present invention utilizes ultrasonic cavitation treatment technology to form cavitation bubbles through the cavitation effect generated in the solution by an ultrasonic pulverizer. With the vibration of the cavitation bubbles and its violent implosion, mechanical shear pressure and violent turbulence are generated, so that the acrylic acid quaternary ammonium salt chitosan molecular chain is broken; at the same time, instantaneous high temperature and high pressure are generated when the cavitation bubble breaks, which can cause the water vapor to thermally dissociate to produce OH free radicals and H atoms. The redox reaction caused by OH free radicals and H atoms can lead to the degradation of acrylic acid quaternary ammonium salt chitosan, thereby shortening the acrylic acid quaternary ammonium salt chitosan molecular chain, weakening the effects of intermolecular hydrogen bonds, and increasing the accessibility and reactivity of quaternary ammonium salts, amino groups, carboxyl groups, and hydroxyl groups in the molecules. Through hydrothermal reaction, the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules are cross-linked with the cationic quaternary ammonium salts and amino groups and electrostatically assembled to form chitosan nanoparticles with small particle size, strong stability and high activity. No chemical cross-linking agent is used in the whole process, and the obtained nano acrylic acid quaternary ammonium salt chitosan has high biological activity, good compatibility, safety and health, and is green and environmentally friendly.
[0032] 6. The present invention makes the nano-acrylic acid quaternary ammonium salt chitosan positively charged at a reaction solution of pH = 4.0 to 5.2, which can significantly increase the electrostatic attraction and grafting reaction efficiency of the positively charged nano-acrylic acid quaternary ammonium salt chitosan to the negatively charged fabric, and the nano-acrylic acid quaternary ammonium salt chitosan has a small particle size and a large specific surface area, and is easy to enter the internal gaps of the fiber and adsorb on the fiber surface, thereby greatly improving the grafting rate of the nano-acrylic acid quaternary ammonium salt chitosan on the fabric and the antibacterial, anti-wrinkle and environmentally friendly dyeing properties; at the same time, no chemical cross-linking agent is used in the grafting reaction between the nano-acrylic acid quaternary ammonium salt chitosan and the fabric, thereby avoiding the negative impact of the cross-linking agent coating on the excellent properties of the fabric and human health.
[0033] 7. The modified fabric of the present invention adopts the heat treatment method of "pre-drying at 50-70°C for 20-35min, stagnating for 5-8min, and then vacuum drying at 45-60°C for 3-6h". The intermittent vacuum drying has the advantages of high efficiency, good temperature control, low energy consumption, uniform heating, simple operation, etc., so that the modified fabric is heated evenly inside and outside, which is conducive to the uniform distribution and firm bonding of nano acrylic acid quaternary ammonium salt chitosan on the fabric surface; at the same time, it avoids the migration phenomenon caused by rapid evaporation of water on the surface of the modified fabric and the uneven distribution and agglomeration of acrylic acid quaternary ammonium salt chitosan nanoparticles grafted on the fabric surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 to Figure 3 It is a schematic diagram of the preparation of nano acrylic acid quaternary ammonium salt chitosan and its grafted silk fabric.
[0035] Figure 4 It is a transmission electron microscope image of the nano acrylic acid quaternary ammonium salt chitosan in test item 3 of the present invention. DETAILED DESCRIPTION
[0036] In order to have a better understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to these embodiments.
[0037] 1. Preparation of active cationic chitosan nanoparticles and their functional finishing fabrics
[0038] Example 1
[0039] (1) Low molecular weight chitosan with a viscosity average molecular weight of 17300 was dissolved in 120 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 2%, 50 mL of anhydrous ethanol was added, and an ethanol solution of vanillin was added dropwise over 25 min under continuous stirring to make the mass ratio of chitosan to vanillin 1:5, and then heated and stirred at 60°C for 8 h. After cooling, 0.4 mol / L NaOH solution was added dropwise with stirring to adjust the pH to neutral, and light yellow chitosan Schiff base was obtained after filtration, ethanol ultrasonic washing (ultrasonic power of 180 W), and vacuum drying.
[0040] (2) Chitosan Schiff base was placed in a three-necked flask, 35 mL of a 0.1% alkaline catalyst 1-butyl-3-methylimidazolium hydroxide ionic liquid solution was added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride was added dropwise within 30 min (the molar ratio of chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride was 1:1), and then stirred at 70 ° C for 1.5 h. The viscous product was precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with a 75% ethanol solution (ultrasonic power of 200 W) for 35 min, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base.
[0041] (3) The quaternary ammonium salt chitosan Schiff base obtained in step (2) was dissolved in 15 mL of an acrylic acid solution having a mass concentration of 15% (the molar ratio of the quaternary ammonium salt chitosan Schiff base to the acrylic acid was 1:5), and then an initiator 4-methoxyphenol (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol was 85:1) and an acidic catalyst ammonium chloride (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride was 1.6:1) were added under microwave irradiation conditions (microwave irradiation power was 480 W, microwave irradiation temperature was 240 °C). 100 ℃) stirring reaction 8min, then add 35mL methanol stirring 1min, finally add acetone precipitation, filter and wash with acetone and ethanol mixture with volume ratio of 1:1, filter with ether, vacuum dry at 40 ℃ for 8h, obtain acrylic acid quaternary ammonium salt chitosan Schiff base powder after ball milling, place in 0.2mol / L hydrochloric acid ethanol solution, evaporate and remove ethanol after rotating stirring for 18h, use acetone precipitation, suction filtration, vacuum drying, ball milling to obtain light yellow acrylic acid quaternary ammonium salt chitosan (active cation chitosan). After testing, the viscosity-average molecular weight of acrylic acid quaternary ammonium salt chitosan (active cation chitosan) obtained in this embodiment is 24590, C3 acrylic acid grafting rate is 66.24%, C2 deacetylation degree is 96.38%, C6 quaternary ammonium salt substitution degree is 70.51%, and solubility in water is 29.04g / 100mL.
[0042] (4) The acrylic acid quaternary ammonium salt chitosan obtained in step (3) was dissolved in an acetic acid solution with a pH of 5.1 to a mass concentration of 0.1%, and ultrasonic cavitation treatment was performed for 6 minutes using an ultrasonic cell crusher with a power of 200 W to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, and then the temperature was raised to 85° C. and stirred for hydrothermal reaction for 50 minutes to crosslink the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules with the cationic quaternary ammonium salt and amino groups and electrostatically assemble to form nanoparticles. After cooling to room temperature and standing for 1.5 hours, a stable and uniform active cationic chitosan nanoparticle dispersion was obtained, and the solution showed opalescence. The average particle size of the active cationic chitosan nanoparticles obtained in this example was 172 nm and the Zeta potential was 31.17 mV as tested by a dynamic light scattering particle size analyzer (DLS). The heavy metal concentration in the remaining solution after adsorption was measured by a flame atomic absorption spectrometer to calculate the adsorption amount of the adsorbent. The active cationic chitosan nanoparticles obtained in this example had a Cu adsorption capacity of 1.5 wt. % and a Cu adsorption capacity of 1.5 wt. % respectively. 2+ and Cr 6+ The adsorption amounts of heavy metals were 62.5 mg / g and 81.9 mg / g respectively.
[0043] The active cationic chitosan nanoparticles obtained in this example are applied to functional finishing of silk fabrics, and the specific steps are as follows:
[0044] (1) The degummed silk fabric is added to a 0.4% active cationic chitosan nanoparticle dispersion according to a bath ratio of 1 g:40 mL, and the pH of the active cationic chitosan nanoparticle dispersion is controlled to 5.1 using acetic acid and sodium acetate buffer. The reaction is stirred continuously at 40° C. for 1.0 h to allow the nano-acrylic acid quaternary ammonium salt chitosan to undergo an amide cross-linking reaction with the silk fabric, and a nano-acrylic acid quaternary ammonium salt chitosan coating is in situ generated on the surface of the silk fabric. The silk fabric is then dipped and rolled twice using an electric rolling mill to achieve a liquid carrying rate of 80%.
[0045] (2) The silk fabric obtained in step (1) is pre-dried at 60° C. for 20 min, left standing for 6 min, and then vacuum dried at 50° C. for 4 h, and the modified silk fabric is filtered and washed with a 45% mass concentration acetone solution to remove unreacted nano-quaternary ammonium salt chitosan, and then washed with deionized water, dehydrated, and air-dried to obtain a silk fabric modified with active cationic chitosan nanoparticles. After testing, the grafting rate of the modified silk fabric of active cationic chitosan nanoparticles obtained in this embodiment is 7.16%, the breaking strength of the modified silk fabric is 447.8N, and the wrinkle recovery angle is 182.3°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus is 93.69%, and the antibacterial rate against Escherichia coli is 92.70%; after the modified silk fabric is dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value is 10.05, and the color fastness is level 4; after being dyed with acid scarlet 3R dye without salt, the dyeing strength K / S value is 14.16, and the color fastness is level 4.
[0046] Example 2
[0047] (1) Low molecular weight chitosan with a viscosity average molecular weight of 12805 was dissolved in 100 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 2.5%, 40 mL of anhydrous ethanol was added, and an ethanol solution of salicylaldehyde was added dropwise over 28 min under continuous stirring to make the mass ratio of chitosan to salicylaldehyde 1:8, and then heated and stirred at 75°C for 10 h. After cooling, 0.4 mol / L NaOH solution was added dropwise with stirring to adjust the pH to neutral, and light yellow chitosan Schiff base was obtained after filtration, ethanol ultrasonic washing (ultrasonic power of 220 W), and vacuum drying.
[0048] (2) Chitosan Schiff base was placed in a three-necked flask, 40 mL of a 0.2% alkaline catalyst 1-butyl-3-methylimidazolium hydroxide ionic liquid solution was added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride was added dropwise within 40 min (the molar ratio of chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride was 1:3), and then stirred at 80°C for 3 h. The viscous product was precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with an ethanol solution with a mass concentration of 80% (ultrasonic power of 240 W) for 35 min, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base.
[0049] (3) The quaternary ammonium salt chitosan Schiff base obtained in step (2) was dissolved in 15 mL of an acrylic acid solution having a mass concentration of 18% (the molar ratio of the quaternary ammonium salt chitosan Schiff base to the acrylic acid was 1:9), and then an initiator 4-methoxyphenol (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol was 90:1) and an acidic catalyst ammonium chloride (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride was 3.2:1) were added under microwave irradiation conditions (the microwave irradiation power was 660 W and the microwave irradiation temperature was 200 °C). The mixture was stirred at 120°C for 12 minutes, and then 40 mL of methanol was added for 2 minutes. Finally, acetone was added for precipitation, and the mixture was filtered and washed with a mixed solution of acetone and ethanol in a volume ratio of 1:1, and filtered with ether, and vacuum dried at 40°C for 8 hours. After ball milling, acrylate quaternary ammonium salt chitosan Schiff base powder was obtained, which was placed in a 0.3 mol / L hydrochloric acid ethanol solution, and ethanol was evaporated and removed after rotating and stirring for 20 hours. A pale yellow acrylate quaternary ammonium salt chitosan (active cation chitosan) was obtained after acetone precipitation, suction filtration, vacuum drying, and ball milling. After testing, the viscosity-average molecular weight of the acrylate quaternary ammonium salt chitosan (active cation chitosan) obtained in the present embodiment was 20549, the C3 acrylic acid grafting rate was 81.68%, the C2 deacetylation degree was 94.12%, the C6 quaternary ammonium salt substitution degree was 87.94%, and the solubility in water was 33.27 g / 100 mL.
[0050] (4) The acrylic acid quaternary ammonium salt chitosan obtained in step (3) was dissolved in an acetic acid solution with a pH of 4.2 to a mass concentration of 0.4%. An ultrasonic cell crusher with a power of 260 W was used to perform ultrasonic cavitation treatment for 8 minutes to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan. The temperature was then raised to 100° C. and stirred for a hydrothermal reaction for 60 minutes to crosslink the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules with the cationic quaternary ammonium salt and amino groups and electrostatically assemble to form nanoparticles. The solution was cooled to room temperature and allowed to stand for 1.5 hours to obtain a stable and uniform dispersion of active cationic chitosan nanoparticles. The solution was opalescent at this time. The average particle size of the active cationic chitosan nanoparticles obtained in this example was 108 nm and the Zeta potential was 43.97 mV as measured by a dynamic light scattering particle size analyzer (DLS). The heavy metal concentration in the remaining solution after adsorption was measured by a flame atomic absorption spectrometer to calculate the adsorption amount of the adsorbent. The active cationic chitosan nanoparticles obtained in this example had a Cu adsorption capacity of 1.5 wt. % and a Cu adsorption capacity of 1.5 wt. % respectively. 2+ and Cr 6+ The adsorption amounts of heavy metals were 90.3 mg / g and 117.9 mg / g respectively.
[0051] The active cationic chitosan nanoparticles obtained in this example are applied to functional finishing of silk fabrics, and the specific steps are as follows:
[0052] (1) The degummed silk fabric is added to a 0.6% active cationic chitosan nanoparticle dispersion according to a bath ratio of 1 g:40 mL, and the pH of the active cationic chitosan nanoparticle dispersion is controlled to 4.4 using acetic acid and sodium acetate buffer. The mixture is stirred and reacted at 60° C. for 2 h to allow the nano-acrylic acid quaternary ammonium salt chitosan to undergo an amide cross-linking reaction with the silk fabric, and a nano-acrylic acid quaternary ammonium salt chitosan coating is in situ generated on the surface of the silk fabric. The silk fabric is then dipped and rolled twice using an electric rolling mill to achieve a liquid carrying rate of 85%.
[0053] (2) The silk fabric obtained in step (1) is pre-dried at 60° C. for 30 min, left for 8 min, and then vacuum dried at 60° C. for 5 h. The modified silk fabric is filtered and washed with a 50% mass concentration acetone solution to remove unreacted nano-quaternary ammonium salt chitosan, and then washed with deionized water, dehydrated, and air-dried to obtain a silk fabric modified with active cationic chitosan nanoparticles. After testing, the grafting rate of the modified silk fabric with active cationic chitosan nanoparticles obtained in this embodiment is 11.28%, the breaking strength of the modified silk fabric is 466.2N, and the wrinkle recovery angle is 201.7°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus is 98.63%, and the antibacterial rate against Escherichia coli is 96.71%; after the modified silk fabric is dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value is 19.37, and the color fastness is level 5; after being dyed with acid scarlet 3R dye without salt, the dyeing strength K / S value is 23.08, and the color fastness is level 5.
[0054] Example 3
[0055] (1) Low molecular weight chitosan with a viscosity average molecular weight of 8702 was dissolved in 85 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 3%, 30 mL of anhydrous ethanol was added, and an ethanol solution of vanillin was added dropwise under continuous stirring within 28 min to make the mass ratio of chitosan to vanillin 1:4, and then heated and stirred at 70°C for 10 h. After cooling, 0.4 mol / L NaOH solution was added dropwise with stirring to adjust the pH to neutral, and light yellow chitosan Schiff base was obtained after filtration, ethanol ultrasonic washing (ultrasonic power of 240 W), and vacuum drying.
[0056] (2) Chitosan Schiff base was placed in a three-necked flask, 45 mL of a 0.3% alkaline catalyst 1-butyl-3-methylimidazolium hydroxide ionic liquid solution was added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride was added dropwise within 40 min (the molar ratio of chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride was 1:4), and then stirred at 85 ° C for 3 h. The viscous product was precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with a 90% ethanol solution (ultrasonic power of 210 W) for 38 min, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base.
[0057] (3) The quaternary ammonium salt chitosan Schiff base obtained in step (2) was dissolved in 15 mL of an acrylic acid solution having a mass concentration of 18% (the molar ratio of the quaternary ammonium salt chitosan Schiff base to the acrylic acid was 1:6), and then an initiator 4-methoxyphenol (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol was 95:1) and an acidic catalyst ammonium chloride (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride was 4:1) were added under microwave irradiation conditions (the microwave irradiation power was 660 W and the microwave irradiation temperature was 120 ℃) stirring reaction 10min, then add 40mL methanol stirring 3min, finally add acetone precipitation, filter and wash with acetone and ethanol mixture with volume ratio of 1:1, use ether suction filtration, 40 ℃ vacuum drying 9h, obtain acrylic acid quaternary ammonium salt chitosan Schiff base powder after ball milling, place in 0.3mol / L hydrochloric acid ethanol solution, evaporate and remove ethanol after rotating stirring for 20h, use acetone precipitation, suction filtration, vacuum drying, ball milling to obtain light yellow acrylic acid quaternary ammonium salt chitosan (active cation chitosan). After testing, the viscosity-average molecular weight of acrylic acid quaternary ammonium salt chitosan (active cation chitosan) obtained in this embodiment is 15310, C3 position acrylic acid grafting rate is 75.32%, C2 position deacetylation degree is 95.40%, C6 position quaternary ammonium salt substitution degree is 81.07%, and solubility in water is 35.84g / 100mL.
[0058] (4) The acrylic acid quaternary ammonium salt chitosan obtained in step (3) was dissolved in an acetic acid solution with a pH of 3.6 to make its mass concentration 0.6%, and ultrasonic cavitation treatment was performed for 8 minutes using an ultrasonic cell crusher with a power of 280W to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, and then the temperature was raised to 100°C and stirred for hydrothermal reaction for 70 minutes to make the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules cross-linked with the cationic quaternary ammonium salt and amino groups and electrostatically assembled to form nanoparticles, and cooled to room temperature and allowed to stand for 1.5 hours to obtain a stable and uniform active cationic chitosan nanoparticle dispersion, at which time the solution showed opalescence; the average particle size of the active cationic chitosan nanoparticles obtained in this example was 137nm and the Zeta potential was 36.52mV as tested by a dynamic light scattering particle size analyzer (DLS). The heavy metal concentration in the remaining solution after adsorption was measured by a flame atomic absorption spectrometer to calculate the adsorption amount of the adsorbent. The active cationic chitosan nanoparticles obtained in this example had a Cu adsorption capacity of 1.50g / cm2. 2+ and Cr 6+ The adsorption amounts of heavy metals were 81.8 mg / g and 92.3 mg / g respectively.
[0059] The active cationic chitosan nanoparticles obtained in this example are applied to functional finishing of wool fabrics, and the specific steps are as follows:
[0060] (1) The wool fabric after scouring and desizing was added into a 0.6% active cationic chitosan nanoparticle dispersion at a bath ratio of 1 g:50 mL, and the pH of the active cationic chitosan nanoparticle dispersion was controlled to 4.2 using acetic acid and sodium acetate buffer. The mixture was stirred and reacted at 60° C. for 3 h to allow the nano-acrylic acid quaternary ammonium salt chitosan to undergo an amide cross-linking reaction with the wool fabric. A nano-acrylic acid quaternary ammonium salt chitosan coating was in situ generated on the surface of the wool fabric. The fabric was then dipped and rolled twice using an electric rolling mill to achieve a liquid carrying rate of 85%.
[0061] (2) The wool fabric obtained in step (1) is pre-dried at 60° C. for 30 min, left to stand for 8 min, and then vacuum dried at 60° C. for 4 h. The modified wool fabric is filtered and washed with a 50% mass concentration acetone solution to remove unreacted nano-quaternary ammonium salt chitosan, and then washed with deionized water, dehydrated, and air-dried to obtain the active cationic chitosan nanoparticle modified wool fabric. After testing, the grafting rate of the wool fabric modified with active cationic chitosan nanoparticles obtained in this embodiment is 8.94%, the breaking strength of the modified wool fabric is 382.6N, and the wrinkle recovery angle is 241.5°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus is 94.83%, and the antibacterial rate against Escherichia coli is 93.61%; after the modified wool fabric is dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value is 13.62, and the color fastness is level 4; after being dyed with acid scarlet 3R dye without salt, the dyeing strength K / S value is 16.39, and the color fastness is level 5.
[0062] Example 4
[0063] (1) Low molecular weight chitosan with a viscosity average molecular weight of 10625 was dissolved in 90 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 3%, 40 mL of anhydrous ethanol was added, and an ethanol solution of salicylaldehyde was added dropwise over 30 min under continuous stirring to make the mass ratio of chitosan to salicylaldehyde 1:6. The mixture was then heated and stirred at 70°C for 12 h. After cooling, 0.4 mol / L NaOH solution was added dropwise with stirring to adjust the pH to neutral. The mixture was filtered, washed with ethanol ultrasound (ultrasonic power of 210 W), and vacuum dried to obtain a light yellow chitosan Schiff base.
[0064] (2) Chitosan Schiff base was placed in a three-necked flask, 50 mL of a 0.36% alkaline catalyst 1-butyl-3-methylimidazolium hydroxide ionic liquid solution was added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride was added dropwise within 45 min (the molar ratio of chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride was 1:5), and then stirred at 80°C for 4 h. The viscous product was precipitated and filtered with anhydrous ethanol, and then ultrasonically washed with an ethanol solution with a mass concentration of 80% (ultrasonic power of 260 W) for 40 min, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base.
[0065] (3) The quaternary ammonium salt chitosan Schiff base obtained in step (2) was dissolved in 15 mL of an acrylic acid solution having a mass concentration of 20% (the molar ratio of the quaternary ammonium salt chitosan Schiff base to the acrylic acid was 1:8), and then an initiator 4-methoxyphenol (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol was 95:1) and an acidic catalyst ammonium chloride (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride was 4.6:1) were added under microwave irradiation conditions (the microwave irradiation power was 660 W and the microwave irradiation temperature was 120 ℃) stirring reaction 12min, then add 40mL methanol stirring 3min, finally add acetone precipitation, filter and wash with acetone and ethanol mixture with volume ratio of 1:1, use ether suction filtration, 40 ℃ vacuum drying 10h, after ball milling, obtain acrylic acid quaternary ammonium salt chitosan Schiff base powder, place in 0.32mol / L hydrochloric acid ethanol solution, after rotating stirring 20h, evaporate and remove ethanol, use acetone precipitation, suction filtration, vacuum drying, ball milling to obtain light yellow acrylic acid quaternary ammonium salt chitosan (active cation chitosan). After testing, the viscosity-average molecular weight of acrylic acid quaternary ammonium salt chitosan (active cation chitosan) obtained in this embodiment is 17218, C3 acrylic acid grafting rate is 78.39%, C2 deacetylation degree is 95.08%, C6 quaternary ammonium salt substitution degree is 84.50%, and solubility in water is 34.66g / 100mL.
[0066] (4) The acrylic acid quaternary ammonium salt chitosan obtained in step (3) was dissolved in an acetic acid solution with a pH of 3.8 to make its mass concentration 0.8%, and ultrasonic cavitation treatment was performed for 10 minutes using an ultrasonic cell crusher with a power of 250W to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, and then the temperature was raised to 105°C and stirred for 80 minutes for hydrothermal reaction to make the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules cross-linked with the cationic quaternary ammonium salt and amino groups and electrostatically assembled to form nanoparticles, and the solution was cooled to room temperature and allowed to stand for 2 hours to obtain a stable and uniform active cationic chitosan nanoparticle dispersion, at which time the solution showed opalescence; the average particle size of the active cationic chitosan nanoparticles obtained in this example was 121nm and the Zeta potential was 40.27mV as tested by a dynamic light scattering particle size analyzer (DLS). The heavy metal concentration in the remaining solution after adsorption was measured by a flame atomic absorption spectrometer to calculate the adsorption amount of the adsorbent. The active cationic chitosan nanoparticles obtained in this example had a Cu adsorption capacity of 1.547 W. 2+ and Cr 6+ The adsorption amounts of heavy metals were 90.2 mg / g and 102.8 mg / g respectively.
[0067] The active cationic chitosan nanoparticles obtained in this example are applied to functional finishing of 60% silk / 40% viscose blended fabric, and the specific steps are as follows:
[0068] (1) After being scoured, desized and degummed, a 60% silk / 40% viscose blended fabric was added to a 0.7% active cationic chitosan nanoparticle dispersion at a bath ratio of 1 g:50 mL, and the pH of the active cationic chitosan nanoparticle dispersion was controlled to 4.0 using acetic acid and sodium acetate buffer. The mixture was stirred at 60° C. for 4 h to allow the nano-acrylic acid quaternary ammonium salt chitosan to cross-link with the 60% silk / 40% viscose blended fabric, and a nano-acrylic acid quaternary ammonium salt chitosan coating was in situ generated on the surface of the blended fabric. The fabric was then dipped and rolled twice using an electric rolling mill to achieve a liquid carrying rate of 90%.
[0069] (2) The blended fabric obtained in step (1) is pre-dried at 60° C. for 32 min, left standing for 8 min, and then vacuum dried at 60° C. for 5 h. The modified blended fabric is washed by filtration with a 60% mass concentration acetone solution to remove unreacted nano-quaternary ammonium salt chitosan, and then washed with deionized water, dehydrated, and air-dried to obtain an active cationic chitosan nanoparticle modified blended fabric. After testing, the grafting rate of the modified blended fabric of active cationic chitosan nanoparticles obtained in this embodiment is 9.62%, the breaking strength of the modified blended fabric is 409.3N, and the wrinkle recovery angle is 193.6°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus is 96.05%, and the antibacterial rate against Escherichia coli is 94.91%; after the modified blended fabric is dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value is 14.24, and the color fastness is level 5; after being dyed with acid red 3R dye without salt, the dyeing strength K / S value is 18.65, and the color fastness is level 5.
[0070] Comparative Example 1
[0071] Preparation of active cationic chitosan nanoparticles (without adding acrylic acid)
[0072] (1) Low molecular weight chitosan with a viscosity average molecular weight of 12805 was dissolved in 100 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 2.5%, 40 mL of anhydrous ethanol was added, and an ethanol solution of salicylaldehyde was added dropwise over 28 min under continuous stirring to make the mass ratio of chitosan to salicylaldehyde 1:8, and then heated and stirred at 75°C for 10 h. After cooling, 0.4 mol / L NaOH solution was added dropwise with stirring to adjust the pH to neutral, and light yellow chitosan Schiff base was obtained after filtration, ethanol ultrasonic washing (ultrasonic power of 220 W), and vacuum drying.
[0073] (2) Chitosan Schiff base was placed in a three-necked flask, 40 mL of a 0.2% alkaline catalyst 1-butyl-3-methylimidazolium hydroxide ionic liquid solution was added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride was added dropwise within 40 min (the molar ratio of chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride was 1:3), and then stirred at 80°C for 3 h. The viscous product was precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with an ethanol solution with a mass concentration of 80% (ultrasonic power of 240 W) for 35 min, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base.
[0074] (3) The quaternary ammonium salt chitosan Schiff base powder obtained in step (2) is placed in a 0.3 mol / L hydrochloric acid ethanol solution, and the ethanol is evaporated and removed after rotary stirring for 20 hours, and a light yellow quaternary ammonium salt chitosan is obtained after acetone precipitation, suction filtration, vacuum drying, and ball milling. After testing, the viscosity-average molecular weight of the quaternary ammonium salt chitosan obtained in this embodiment is 18426, the deacetylation degree at C2 is 94.12%, the quaternary ammonium salt substitution degree at C6 is 87.94%, and the solubility in water is 19.48 g / 100 mL.
[0075] (4) The quaternary ammonium salt chitosan obtained in step (3) is dissolved in an acetic acid solution with a pH of 4.2 to make its mass concentration 0.4%, and ultrasonic cavitation treatment is performed for 8 minutes using an ultrasonic cell crusher with a power of 260W to break the quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, and then the temperature is raised to 100°C and stirred for a hydrothermal reaction for 60 minutes to make the hydroxyl groups in the quaternary ammonium salt chitosan molecules electrostatically assemble with the cationic quaternary ammonium salt and amino groups to form nanoparticles, and the quaternary ammonium salt chitosan nanoparticle dispersion is obtained after cooling to room temperature and standing for 1.5 hours. At this time, the solution exhibits opalescence; the average particle size of the quaternary ammonium salt chitosan nanoparticles obtained in this embodiment is 604nm and the Zeta potential is 16.19mV after testing by a dynamic light scattering particle size analyzer (DLS). The heavy metal concentration in the remaining solution after adsorption is measured by a flame atomic absorption spectrometer to calculate the adsorption amount of the adsorbent. The quaternary ammonium salt chitosan nanoparticles obtained in this embodiment have an adsorption capacity of Cu 2+ and Cr 6+ The adsorption amounts of heavy metals were 39.5 mg / g and 51.3 mg / g respectively.
[0076] Comparative Example 2
[0077] Preparation of active cationic chitosan nanoparticles (without ultrasonic cell crusher treatment)
[0078] (1) Low molecular weight chitosan with a viscosity average molecular weight of 12805 was dissolved in 100 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 2.5%, 40 mL of anhydrous ethanol was added, and an ethanol solution of salicylaldehyde was added dropwise over 28 min under continuous stirring to make the mass ratio of chitosan to salicylaldehyde 1:8, and then heated and stirred at 75°C for 10 h. After cooling, 0.4 mol / L NaOH solution was added dropwise with stirring to adjust the pH to neutral, and light yellow chitosan Schiff base was obtained after filtration, ethanol ultrasonic washing (ultrasonic power of 220 W), and vacuum drying.
[0079] (2) Chitosan Schiff base was placed in a three-necked flask, 40 mL of a 0.2% alkaline catalyst 1-butyl-3-methylimidazolium hydroxide ionic liquid solution was added and stirred to disperse evenly, 2,3-epoxypropyltrimethylammonium chloride was added dropwise within 40 min (the molar ratio of chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride was 1:3), and then stirred at 80°C for 3 h. The viscous product was precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with an ethanol solution with a mass concentration of 80% (ultrasonic power of 240 W) for 35 min, and then extracted, vacuum dried, and ball milled to obtain an orange quaternary ammonium salt chitosan Schiff base.
[0080] (3) The quaternary ammonium salt chitosan Schiff base obtained in step (2) was dissolved in 15 mL of an acrylic acid solution having a mass concentration of 18% (the molar ratio of the quaternary ammonium salt chitosan Schiff base to the acrylic acid was 1:9), and then an initiator 4-methoxyphenol (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol was 90:1) and an acidic catalyst ammonium chloride (the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride was 3.2:1) were added under microwave irradiation conditions (the microwave irradiation power was 660 W and the microwave irradiation temperature was 200 °C). The mixture was stirred at 120°C for 12 minutes, and then 40 mL of methanol was added for 2 minutes. Finally, acetone was added for precipitation, and the mixture was filtered and washed with a mixture of acetone and ethanol in a volume ratio of 1:1, and filtered with ether, and vacuum dried at 40°C for 8 hours. After ball milling, acrylate quaternary ammonium salt chitosan Schiff base powder was obtained, which was placed in a 0.3 mol / L hydrochloric acid ethanol solution, and the ethanol was evaporated after rotating and stirring for 20 hours. A pale yellow acrylate quaternary ammonium salt chitosan (active cationic chitosan) was obtained after acetone precipitation, suction filtration, vacuum drying, and ball milling. After testing, the viscosity-average molecular weight of the acrylate quaternary ammonium salt chitosan (active cationic chitosan) obtained in this comparative example was 20549, the C3 acrylic acid grafting rate was 81.68%, the C2 deacetylation degree was 94.12%, the C6 quaternary ammonium salt substitution degree was 87.94%, and the solubility in water was 33.27 g / 100 mL.
[0081] (4) Dissolve the acrylic acid quaternary ammonium salt chitosan obtained in step (3) in an acetic acid solution with a pH of 4.2 to a mass concentration of 0.4%, then heat to 100°C and stir for a hydrothermal reaction for 60 minutes, so that the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules are cross-linked with the cationic quaternary ammonium salt and the amino group and electrostatically assembled to form nanoparticles, and then cool to room temperature and stand for 1.5 hours to obtain an active cationic chitosan nanoparticle dispersion, at which time the solution exhibits opalescence; tested by a dynamic light scattering particle size analyzer (DLS), the average particle size of the active cationic chitosan nanoparticles obtained in this example is 373nm and the Zeta potential is 22.34mV. The heavy metal concentration in the remaining solution after adsorption is measured by a flame atomic absorption spectrometer, and the adsorption amount of the adsorbent is calculated. The nano-active cationic chitosan obtained in this example has an adsorption capacity of Cu 2+ and Cr 6+ The adsorption amounts of heavy metals were 47.6 mg / g and 62.8 mg / g respectively.
[0082] Comparative Example 3 (without modification and finishing of nano acrylic acid quaternary ammonium salt chitosan)
[0083] Unmodified silk fabric:
[0084] The silk fabric was degummed to obtain a silk fabric sample. According to the test, the unmodified silk fabric obtained in this comparative example had a breaking strength of 421.6N and a wrinkle recovery angle of 163.2°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus was 23.69%, and the antibacterial rate against Escherichia coli was 17.54%; after the unmodified silk fabric was dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value was 2.36, and the color fastness was grade 2; after the unmodified silk fabric was dyed with acid scarlet 3R dye without salt, the dyeing strength K / S value was 3.50, and the color fastness was grade 2.
[0085] Unmodified wool fabric:
[0086] The wool fabric was subjected to scouring and desizing treatment to obtain a wool fabric sample. After testing, the unmodified wool fabric obtained in this comparative example had a breaking strength of 360.5N and a wrinkle recovery angle of 198.2°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus was 27.34%, and the antibacterial rate against Escherichia coli was 25.08%; after the unmodified wool fabric was dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value was 3.07, and the color fastness was grade 2; after the unmodified wool fabric was dyed with acid scarlet 3R dye without salt, the dyeing strength K / S value was 4.61, and the color fastness was grade 3.
[0087] Unmodified 60% Silk / 40% Viscose Blended Fabric:
[0088] The 60% silk / 40% viscose blended fabric was subjected to scouring, desizing and degumming treatment to obtain a blended fabric sample. After testing, the unmodified blended fabric obtained in this comparative example had a breaking strength of 388.5N and a wrinkle recovery angle of 170.3°; after 100 times of washing, the antibacterial rate against Staphylococcus aureus was 27.96%, and the antibacterial rate against Escherichia coli was 24.53%; after the unmodified blended fabric was dyed with active dark blue A-2GLN dye without salt, the dyeing strength K / S value was 3.74, and the color fastness was grade 3; after the unmodified blended fabric was dyed with acid scarlet 3R dye without salt, the dyeing strength K / S value was 1.69, and the color fastness was grade 2.
[0089] 2. Testing the samples obtained in the above examples
[0090] Test Item 1: Add different moles of acrylic acid to react with quaternary ammonium salt chitosan Schiff base, then remove the Schiff base protection, ultrasonic cell crusher ultrasonic cavitation treatment, and then hydrothermal reaction to form nanoparticles through electrostatic assembly to form particle size test
[0091] The molar ratio of the quaternary ammonium salt chitosan Schiff base to acrylic acid in Example 2 was adjusted to 1:0, 1:4, 1:6, 1:9, 1:10, and the obtained nanoparticle dispersion was tested by dynamic light scattering (DLS). The test results are shown in Table 1.
[0092] Table 1 Average particle size of acrylic acid quaternary ammonium salt chitosan nanoparticles
[0093]
[0094] As shown in Table 1, the chitosan nanoparticles prepared by reacting acrylic acid with quaternary ammonium salt chitosan Schiff base in different molar ratios, removing the Schiff base protection, ultrasonic cavitation treatment by ultrasonic cell crusher, and hydrothermal reaction by electrostatic assembly have small particle size, uniform size, low dispersion coefficient and strong stability. Compared with the particle size of 604 nm of chitosan nanoparticles obtained without adding acrylic acid, the average particle size of chitosan nanoparticles added with acrylic acid is about 106-181 nm, the nano size is significantly reduced, and the distribution is more uniform, indicating that the anionic carboxyl group in the acrylic acid quaternary ammonium salt chitosan molecule can undergo cross-linking reaction with the cationic quaternary ammonium salt and the amino group, and further electrostatic assembly is formed to form chitosan nanoparticles with smaller size, uniform particle size, strong stability and high biological activity, which has a wide range of applications.
[0095] Test Item 2: Stability Test of Nanoparticles
[0096] 10 mL of each chitosan nanodispersion sample of Comparative Examples 1-2 and Examples 2-4 were taken, respectively, and placed in a 20 mL vial, the bottle mouth was sealed, and placed at room temperature for 14 days. The average particle size and Zeta potential of the chitosan nanoparticles were measured at the specified time, and the appearance changes of each sample were compared. The test results are shown in Table 2.
[0097] Table 2 Changes in particle size and potential of chitosan nanoparticles before and after 14 days of standing
[0098]
[0099]
[0100] The data in Table 2 show that the present invention first uses acrylic acid to react with quaternary ammonium salt chitosan Schiff base in different molar ratios, then removes Schiff base protection, and undergoes ultrasonic cavitation treatment with an ultrasonic cell crusher to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, and then undergoes hydrothermal reaction to crosslink the anionic carboxyls in the acrylic acid quaternary ammonium salt chitosan molecules with the cationic quaternary ammonium salt and amino groups and electrostatically assemble to form nanoparticles, which significantly improves the particle size and stability of the nanoparticles, and the crosslinking and electrostatic self-assembly of the anionic carboxyls of the acrylic acid quaternary ammonium salt chitosan and the ultrasonic cavitation treatment will significantly affect the particle size, potential, stability and functional effect of the nanoparticles. By optimizing the ultrasonic cavitation treatment power and time, and the molar addition ratio of acrylic acid, the acrylic acid quaternary ammonium salt chitosan nanoparticles prepared by the present invention have more ideal particle size, potential and stability and more durable and efficient functionality.
[0101] Test Item 3: Transmission Electron Microscopy Analysis of Nano-Acrylic Acid Quaternary Ammonium Salt Chitosan
[0102] TEM was used to observe the microscopic morphology of acrylic acid-based quaternary ammonium salt chitosan nanoparticles. Four samples of acrylic acid-based quaternary ammonium salt chitosan nanoparticles were taken: the first sample was a nano-active cationic chitosan a with an average particle size of 604 nm obtained by the method of Comparative Example 1 without adding acrylic acid, the second sample was a nano-active cationic chitosan b with an average particle size of 373 nm obtained by the method of Comparative Example 2 without using an ultrasonic cell crusher, the third sample was a nano-active cationic chitosan c with an average particle size of 108 nm obtained by the method of Example 2, and the fourth sample was a nano-active cationic chitosan d with an average particle size of 137 nm obtained by the method of Example 3. The test results are shown in Table 1. Figure 4 (a)~(d).
[0103] Depend on Figure 4It is shown that the active cationic chitosan molecules without acrylic acid lack the cross-linking and electrostatic assembly formed by the anionic carboxyl group and the cationic quaternary ammonium salt and amino group, resulting in larger nanoparticle size, more nanoparticle agglomeration, and poor stability (see Figure 4 a); At the same time, the molecular weight of acrylic acid quaternary ammonium salt chitosan that is not subjected to ultrasonic cavitation treatment using an ultrasonic cell crusher is relatively large, and the particle size of the nanoparticles formed by hydrothermal reaction is also relatively large. The acrylic acid quaternary ammonium salt chitosan solution is subjected to ultrasonic cavitation treatment using an ultrasonic cell crusher to break the molecular chain of acrylic acid quaternary ammonium salt chitosan to form small molecular chitosan, and then the hydrothermal reaction causes the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules to crosslink with the cationic quaternary ammonium salt and amino groups and electrostatically assemble to form stable, uniform, and small-size active cationic chitosan nanoparticles (see Figure 4 c and d).
[0104] In summary, a triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) solution of low molecular weight chitosan is reacted with an ethanol solution of an aldehyde compound to form a Schiff base protection at the amino group at the C2 position of chitosan, and then a nucleophilic substitution reaction is carried out at the C6 position of chitosan with 2,3-epoxypropyltrimethylammonium chloride under an alkaline catalyst, and then a chemical initiator is added to graft with acrylic acid at the C3 position of chitosan, and then the Schiff base protection at the C2 position of chitosan is removed, and the carboxylate anion of acrylic acid and the cation of chitosan are cross-linked and self-assembled by a hydrothermal reaction to obtain a cationic chitosan nanoparticle with strong stability, small particle size, uniform distribution, and high efficiency and long-lasting function. The method of the present invention has a simple preparation process, mild and controllable reaction conditions, fast catalytic substitution reaction rate, low cost, and the prepared nano cationic chitosan has high reaction activity, is green and environmentally friendly, and has long-lasting antibacterial effect. The nanoparticles contain a large amount of quaternary ammonium salts and amino dicationic groups and carboxyl groups, and have great application potential in the fields of adsorption of dyes, heavy metals, and functional finishing of textiles.
[0105] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An active cationic chitosan nanoparticle, characterized in that: The active cationic chitosan nanoparticles are prepared by reacting a triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) solution of low molecular weight chitosan with an ethanol solution of an aldehyde compound to form a Schiff base protection at the amino group at the C2 position of chitosan, then reacting with 2,3-epoxypropyltrimethylammonium chloride in the presence of an alkaline catalyst to carry out a nucleophilic substitution reaction at the C6 position of chitosan, then adding a chemical initiator to graft with acrylic acid at the C3 position of chitosan, then removing the Schiff base protection at the C2 position of chitosan, and cross-linking the carboxylate anion of acrylic acid with the cation of chitosan through a hydrothermal reaction to obtain the active cationic chitosan nanoparticles.
2. A method for preparing active cationic chitosan nanoparticles according to claim 1, characterized in that: The steps include: (1) Dissolving low molecular weight chitosan with a viscosity average molecular weight of 6300 to 18200 in 80 to 120 mL of triethylamine hydrogen sulfate ionic liquid ([(C2H5)3NH]HSO4) to prepare a chitosan solution with a mass concentration of 1% to 4%, adding 20 to 60 mL of anhydrous ethanol, and dropping an ethanol solution of an aldehyde compound within 20 to 30 minutes under continuous stirring to make the mass ratio of chitosan to the aldehyde compound be 1:1 to 9, then heating and stirring at 60 to 80° C. for 8 to 12 hours, and after cooling and stirring, dropping 0.4 mol / L NaOH solution to adjust the pH to neutral, filtering, washing with ethanol ultrasonically, and vacuum drying to obtain a chitosan Schiff base; the aldehyde compound is salicylaldehyde, vanillin, cinnamaldehyde or fatty aldehyde; (2) The chitosan Schiff base is placed in a three-necked flask, 30-50 mL of an alkaline catalyst solution with a mass concentration of 0.08-0.4% is added and stirred to disperse uniformly, 2,3-epoxypropyltrimethylammonium chloride is added dropwise within 30-50 minutes, and then stirred and reacted at 60-90° C. for 1-4 hours, and the obtained viscous product is precipitated with anhydrous ethanol, filtered, and then ultrasonically washed with an ethanol solution with a mass concentration of 75-90% for 30-40 minutes, and then extracted, vacuum dried, and ball milled to obtain a quaternary ammonium salt chitosan Schiff base; the molar ratio of the chitosan Schiff base to 2,3-epoxypropyltrimethylammonium chloride is 1:0.5-5, and the alkaline catalyst is 1-butyl-3-methylimidazolium hydroxide ionic liquid ([Bmim]OH); (3) The quaternary ammonium salt chitosan Schiff base obtained in step (2) is dissolved in 15 mL of an acrylic acid solution having a mass concentration of 10 to 20%, and then an initiator 4-methoxyphenol and an acidic catalyst ammonium chloride are added, and the mixture is stirred for reaction for 5 to 15 minutes under microwave irradiation, followed by adding 30 to 45 mL of methanol and stirring for 1 to 3 minutes, and finally acetone is added for precipitation, and the mixture is filtered and washed with a mixed solution of acetone and ethanol in a volume ratio of 1:1, and filtered with ether, and vacuum dried at 40 to 60° C. for 8 to 10 hours, and ball milled to obtain an acrylic acid-based quaternary ammonium The quaternary ammonium salt chitosan Schiff base powder is placed in a 0.2-0.4 mol / L hydrochloric acid ethanol solution, and the ethanol is evaporated after rotating and stirring for 18-20 hours, and the quaternary ammonium salt chitosan is obtained after acetone precipitation, suction filtration, vacuum drying, and ball milling; the molar ratio of the quaternary ammonium salt chitosan Schiff base to acrylic acid is 1:4-10, the mass ratio of the quaternary ammonium salt chitosan Schiff base to the initiator 4-methoxyphenol is 80-100:1, and the mass ratio of the quaternary ammonium salt chitosan Schiff base to the acidic catalyst ammonium chloride is 1.2-5.8:1; (4) dissolving the acrylic acid quaternary ammonium salt chitosan obtained in step (3) in an acetic acid solution with a pH of 3.2 to 5.4 to make its mass concentration 0.03 to 1.2%, performing ultrasonic cavitation treatment for 6 to 10 minutes using an ultrasonic cell crusher with a power of 160 to 300 W to break the acrylic acid quaternary ammonium salt chitosan molecular chain to form small molecule chitosan, then heating to 80 to 110° C. and stirring for 40 to 90 minutes to perform hydrothermal reaction to make the anionic carboxyl groups in the acrylic acid quaternary ammonium salt chitosan molecules cross-linked with the cationic quaternary ammonium salt and amino groups and electrostatically assemble to form nanoparticles, cooling to room temperature and standing for 1 to 2 hours to obtain a stable and uniform active cationic chitosan nanoparticle dispersion; the active cationic chitosan nanoparticles have an average particle size of 106 to 181 nm and a Zeta potential of 28.65 to 45.39 mV.
3. The preparation method according to claim 2, characterized in that: The viscosity-average molecular weight of the acrylic acid quaternary ammonium salt chitosan in step (3) is 9620-26075, the grafting rate of acrylic acid at C3 is 61.03-82.37%, the deacetylation degree at C2 is ≥92.41%, the substitution degree of quaternary ammonium salt at C6 is 69.60-89.16%, and the solubility in water is ≥27.58 g / 100 mL; the structural formula of the acrylic acid quaternary ammonium salt chitosan is as follows:
4. The preparation method according to claim 2, characterized in that: In step (1) and step (2), the ultrasonic power of ultrasonic washing is 160-280W; in step (3), the microwave radiation power is 420-780W, and the microwave radiation temperature is 100-120°C.
5. A method for preparing a fabric modified with active cationic chitosan nanoparticles, characterized in that: The steps include: (1) adding the fabric after scouring, desizing or degumming to a dispersion of active cationic chitosan nanoparticles according to claim 1 with a mass concentration of 0.2-1.2% at a bath ratio of 1 g:30-50 mL, and stirring the mixture at 30-60° C. for 0.5-4 h to allow the active cationic chitosan nanoparticles to undergo an amide crosslinking reaction with the fabric, thereby forming a nano acrylic acid-based quaternary ammonium salt chitosan coating on the fabric surface in situ, and then using an electric padder to perform double dipping and double rolling to make the liquid carrying rate of the modified fabric 70-90%; (2) The fabric obtained in step (1) is pre-dried at 50-70° C. for 20-35 min, left standing for 5-8 min, and then vacuum dried at 45-60° C. for 3-6 h, and the modified fabric is washed by filtration with an acetone solution having a mass concentration of 40-60% to remove unreacted active cationic chitosan nanoparticles, and then washed with deionized water, dehydrated, and air-dried to obtain a fabric modified with active cationic chitosan nanoparticles.
6. The preparation method according to claim 5, characterized in that: In step (1), acetic acid and sodium acetate buffer are used to control the pH of the active cationic chitosan nanoparticle dispersion to 4.0-5.
2.
7. The preparation method according to claim 5, characterized in that: The loading amount of active cationic chitosan nanoparticles in the modified fabric is 6.94-11.38%.
8. An active cationic chitosan nanoparticle modified fabric obtained by the preparation method according to any one of claims 5 to 7.
9. Use of the fabric modified with active cationic chitosan nanoparticles as claimed in claim 8 in salt-free environmentally friendly dyeing with reactive dyes and acid dyes.
10. The active cationic chitosan nanoparticles according to claim 1 are used to adsorb Cu in wastewater. 2+ and / or Cr 6+ Application of heavy metals.
Citation Information
Patent Citations
Modified tussah silk fabric with functionalized nanometer chitosan and nanometer titanium dioxide
CN102677465B
Cited By
Phosphorylated carboxyl chitosan nanosphere (at) Mxene antibacterial composite flame retardant
CN120040845A
Phosphorylated Carboxylated Chitosan Nanospheres@Mxene Antibacterial Composite Flame Retardant
CN120040845B